ICGPA, IR4.0 and graduate employability from the lens of the academics / Faizah A Majid. - A Majid, Faizah (2018)
This paper focuses on heated issues in the Malaysian public universities of late. Specifically, the paper uncovers the perceptions of a group of lecturers in a selected public university regarding iCGPA, IR4.0 and Graduate Employability. In eliciting relevant data, series of semi-structured interview were conducted. A total of ten lecturers from a faculty volunteered as participants. In collecting the data through the semi-structured interview, saturation stage was achieved at the end of the 5th participant. Anticipating no new themes could emerge from the subsequent interviews upon the saturation stage, it was decided that the research findings would be derived from the relevant excerpts from the existing five interviews. The interviews were done separately, and each lasted between 45 minutes and an hour. In ensuring the trustworthiness of the research findings interpretations, member-checks and an inter-rater were done. The salient findings include frustration over iCGPA implementation and a vague understanding of IR4.0 among the participants. The findings however revealed the participants’ awareness of graduate employability. Most importantly, the findings concluded that though the participants were clear with the importance of graduate employability, they were unsure about iCGPA’s role in enhancing graduate employability and how IR4.0 could be embedded in their syllabus to promote graduate employability. All in all, this paper has confirmed a potential gap between the three main aspects namely; iCGPA, IR4.0 and graduate employability. The implications include the need to revisit the existing curriculum in complementing the training needs of IR4.0 skills, to re-skill lecturers in their teaching approaches and to examine the implementation of iCGPA as a platform to indicate IR4.0 skills and to promote graduate employability. Various parties could benefit from the research findings such as the curriculum developer, the lecturers themselves and most importantly the policymakers.